Prasugrel-related hepatotoxicity - Dogan, Zeki; Mustafa Yurtdas; Gokhan Bektasoglu (Journal of the Pakistan Medical Association, 2022)
Prasugrel is usually preferred over Clopidogrel to reduce the risk of recurrent coronary thrombosis in patients who undergo percutaneous coronary interventions during an acute coronary syndrome owing to its more potent and more rapid antithrombotic activation. Little is known about Prasugrel-induced hepatotoxicity, although mild-to-moderate alanine transaminase (ALT) and gamma glutamyl transpeptidase (GGT) elevations have been noticed in post-marketing surveillance. Herein, we report the case of a patient with Prasugrel-related hepatotoxicity that was reverted after switching from Prasugrel to Ticagrelor. Keywords: Percutanous coronary interventions, antiplatelet drug, Prasugrel, hepatotoxicity.